Securing SQL server protecting your database from attackers - Cherry, Denny (Syngress, 2011)
There is a lot at stake for administrators taking care of servers, since they house sensitive data like credit cards, social security numbers, medical records, and much more. In Securing SQL Server you will learn about the potential attack vectors that can be used to break into your SQL Server database, and how to protect yourself from these attacks. Written by a Microsoft SQL Server MVP, you will learn how to properly secure your database, from both internal and external threats. Best practices and specific tricks employed by the author will also be revealed. Learn expert techniques to protect your SQL database environment. Author Denny Cherry is an MVP by Microsoft for his expertise in the SQL Server product Learn expert techniques to protect your SQL database environment Discover how to identify what an intruder accessed or damaged.